Інструменти та методи розробки стартапів в інженерних кластерах - Голик, О. П.; Holyk, O. (ЦНТУ, 2022)
В статті обґрунтовано доцільність вивчення здобувачами вищої освіти дисципліни, яка формує компетентності з розробки інноваційних проєктів. Наведено та розглянуто методологічний інструмент, який дозволяє розробляти стартами та займатися проєктною діяльністю. The article is aimed at reviewing the most effective methods and tools for the making of startups. Relevance of familiarization of students of engineering specialties with these methods lies in the need to acquire knowledge, skills and skills in innovative project activities. As the labors market is constantly changing, employers are interested in graduates who have project skills and practical experience. The article considers soft skills that will be in demand in the coming years for successful professional growth and ability to work in a team. The advantages and disadvantages of teamwork, as well as recommendations for improving the effectiveness of teamwork, are presented. The main obstacles preventing control of the process to develop the startup are mentioned. Methods of planning and control of time, determination of priorities of tasks are considered. To formulate the project name and to form the goals, the main instruments that allow to determine the influence of strong and weak sides (SWOT-analysis) are given. Also the tools of the composition structure of works and the hierarchical structure of works which allow to divide the project into components of tasks and subgoals are considered. Thus, the study of engineering and technical specialities of the methods and tools of making start-ups, presented in the article, will help students to form skills to survive failures, to treat their own mistakes with tolerance, to learn to work in a team in a multidisciplinary environment. As a result, students can take a risk-free trial during their studies at the university, and once they have completed their studies they will be ready to engage in professional activities at once.
Tools and Methods for Developing Startups in Engineering Clusters
Keywords: універсальні навички; командна робота; піраміда Франкліна; матриця Ейзенхауера; закон Парето; діаграма Ґанта; soft skills; teamwork; the Franklin Pyramid; the Eisenhower Matrix; Pareto Principle; Gantt chart